1975
DOI: 10.1159/000459829
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Development of Infant M. arctoides Fed a Standardized Diet

Abstract: Infant Macaco arctoides were reared under standard conditions. Changes in body weight, body length, head circumference, hematologic status and serum proteins during the first year of life were defined in relation to the ad libitum consumption of a standardized milk diet, and compared to those derived from infant M. mulatta. Both sexes consumed a comparable volume of diet per kilogram body weight, but male M. arctoides infants were significantly larger than females in all body dimensions : this finding was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…As is typically the case in humans (Guo et al, 1991), infant rhesus and stumptail macaques (Kerr et al, 1969;Scheffler and Kerr, 1975), cebus monkeys (Fleagle and Samonds, 1975), and chimpanzees (Gavan, 1953), rapid initial growth followed by gradual deceleration was apparent during the first year of life of the six study infants. The one exception was J.J., who maintained a high growth rate in all measures except head circumference, well beyond the time of decelerated growth in the other infants.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…As is typically the case in humans (Guo et al, 1991), infant rhesus and stumptail macaques (Kerr et al, 1969;Scheffler and Kerr, 1975), cebus monkeys (Fleagle and Samonds, 1975), and chimpanzees (Gavan, 1953), rapid initial growth followed by gradual deceleration was apparent during the first year of life of the six study infants. The one exception was J.J., who maintained a high growth rate in all measures except head circumference, well beyond the time of decelerated growth in the other infants.…”
Section: Discussionmentioning
confidence: 59%
“…First-year growth patterns in weight and selected body measurements were studied by Kerr et al (1969) in M. mulatta, Scheffler and Kerr (1975) in M. arctoides, and Fleagle and Samonds (1975) in Cebus albifrons. These studies also aimed to establish normative data and confirmed the general primate infant growth pattern.…”
mentioning
confidence: 99%
“…Over the past seven years, weights of all nonhuman primates in the Primate Behavior Laboratory of Downstate Medical Center have been collected at the time of tuberculin testing twice per year. Other than reports QnMacaca mulatta (7,10), data on developmental weight gain in macaques, as yet, have been focused on major developmental periods such as infancy (2,3,8,9) and puberty (12,13). Our long-term collection of weights provides us with a large sample of laboratory-born animals with which to generate complete developmental weight curves under comparable conditions for two species of macaque, Macaca nemestrina and Macaca radiata.…”
Section: Introductionmentioning
confidence: 99%